Mordred : From Traitorous Son to Prodigious Child-Druid - Martins, Ana Rita (2017)
A character of Arthurian legend, Sir Mordred, King Arthur’s nephew and son, is one of the most famous villains of European imagination. His reputation, though, has not always been so bad. In fact, it was only in 1136, in Historia Regum Britanniae, that Geoffrey of Monmouth identified Mordred as the traitor behind Camelot’s destruction and Arthur’s death. However, Monmouth still depicts Mordred as the King’s nephew. The Vulgate Cycle first introduced the idea that Mordred is Arthur’s son with one of his sisters. Soon, Mordred’s wickedness would be explained by the immoral union he was born from, but can Mordred’s behavior be accounted for by the circumstances of his birth? Starting by analyzing key medieval texts, this paper aims at examining Mordred’s infamous history and work out how and why he has been described as a villain. In addition, attention will be paid to modern adaptations. What has changed when it comes to depicting villains? What medieval characteristics (if any) have been kept?